2013
DOI: 10.1039/c3cp00126a
|View full text |Cite
|
Sign up to set email alerts
|

The CO oxidation mechanism and reactivity on PdZn alloys

Abstract: The effect of Zn on the CO adsorption and oxidation reaction is examined experimentally and theoretically on two PdZn catalysts with different compositions, namely the intermetallic 1:1 β-PdZn and α-PdZn as a solid solution of 9 at% Zn in Pd. These bimetallic catalysts, made using an aerosol derived method, are homogeneous in phase and composition so that the measured reactivity excludes support effects. Both specific reactivities for CO oxidation on these two PdZn catalysts were measured. It was found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 43 publications
6
27
0
Order By: Relevance
“…The IMC formation was discussed to be responsible for a reduced CO binding energy that made O 2 -adsorption more competitive. The same observations were made by Johnson et al [28] who investigated CO-oxidation and CO-adsorption on ␣-and ␤-PdZn and observed 5-10 times higher initial rates for the reaction, compared to pure Pd, however observing also deactivation upon time by zinc oxidation. CO-oxidation in general was intensively studied and discussed as a suitable model reaction for various heterogeneous, catalytic processes [29].…”
Section: Introductionsupporting
confidence: 75%
“…The IMC formation was discussed to be responsible for a reduced CO binding energy that made O 2 -adsorption more competitive. The same observations were made by Johnson et al [28] who investigated CO-oxidation and CO-adsorption on ␣-and ␤-PdZn and observed 5-10 times higher initial rates for the reaction, compared to pure Pd, however observing also deactivation upon time by zinc oxidation. CO-oxidation in general was intensively studied and discussed as a suitable model reaction for various heterogeneous, catalytic processes [29].…”
Section: Introductionsupporting
confidence: 75%
“…In the case of ZnPd, even exposure to carbon monoxide results in structural modifications [83, 84], preventing the use of this frequently used test molecule in heterogeneous catalysis to determine the nature of the surface of ZnPd-based catalysts. Up to now, the behavior of ZnPd under reaction conditions is not at all explored in a systematic way (for a comprehensive review on ZnPd see [85]), but potentially holds the key for a full understanding of the requirements for MSR catalysts and, thus, the development of innovative materials combining higher activity and selectivity.…”
Section: Methanol Steam Reformingmentioning
confidence: 99%
“…[48][49][50][51] There are two proposed mechanisms through which the CO molecule is thought to be oxidized by the O 2 molecule at the catalyst surfaces: the Langmuir-Hinshelwood mechanism and the Eley-Rideal mechanism. In recent years, low-temperature CO oxidation was extensively studied because of the increasing importance of cleaning air and lowering automotive emissions.…”
Section: Activity Of Co Oxidation On H-bnns/cu(111)mentioning
confidence: 99%